Food for thought or food for emotions? An analysis of marketing strategies in television food advertising seen by children in Colombia - Alcides Velasquez; Maria Fernanda Parra; Mercedes Mora-Plazas; Luis Fernando Gómez; Lindsey Smith Taillie; Francesca Renee Dillman Carpentier (Public Health Nutrition, 2023)
Abstract